Mathematical sciences, technology, and economic competitiveness - Glimm, James; Griffiths, Phillip, 1938- (National Academy Press, 1991)
This book describes the contributions of mathematics to the nation's advanced technology and to economic competitiveness. Examples from five industries--aircraft, petroleum, automotive, semiconductor, and telecommunications--illustrate how mathematics enters into and improves industry. Mathematical Sciences, Technology, and Economic Competitiveness addresses these high-technology industries and breadth of mathematical endeavors in the United States as they materially contribute to the technology base from which innovation in these industries flows. The book represents a serious attempt by the mathematics community to bring about an awareness by policymakers of the pervasive influence of mathematics in everyday life.